P POTENSI KANDUNGAN KARAMUNTING (Rhodomyrtus tomentosa) DALAM BERIKATAN DENGAN HMG-CoA REDUKTASE - Kunti - Nastiti; Samsul Hadi (LPPM Universitas Sari Mulia, 2021)
Background : Hyperlipidemia is the medical term for abnormally high levels of fats (lipids) in the blood. The two types of lipids found in the blood are triglycerides and cholesterol. The enzyme that plays a role in cholesterol regulation is HMG-CoA reductase. Objective : The purpose of this study was to find the content of karamunting compounds that have stability in interactions with HMG-CoA reductase. Method : The research method is to see the probability of activity with webservices, protein-compound interactions with PLANTS, visualization with Discovery studio. Results : The results of this study have a minimum activity probability of 0.5, namely -tocopherol-quinone, naringenin, quercetin, -tocopherol A, verimol K. The docking score is at least 80% against the reference ligand, namely -tocopherol-quinone (100%), blumeatin (82%), rhodomyrtosone C (80%), tetrahydroxyflavanone (81%), -tocopherol A (86%). Conclusion: The conclusion of this study is the probability of activity of the most potent compound is -tocopherol A and the interaction stability result is -tocopherol-quinone.